Value preconditions and the educational guidelines of the open society (Actual Problems of Mind, 2021)
The article is devoted to the issue of open society, its values, and the implementation of thereof in education. It emphasizes the importance of this concept in the context of the development of key problems of modern philosophy. The paper considers the system of ideals and norms of the open society and substantiates their interrelation with the principles of rationality. It analyzes the value principles of the functioning of the education system and the possibilities of its reformation based on critical rationalism. It outlines the following problems: the methodology of social reforms, the state control over education, the spread of anti-egalitarian tendencies in society, the regulation of the educational process, the introduction of a person-centred approach to learning, the approach focused on critical discussion of essential social issues, the problem of the development of the skills, necessary for participation in the democratic life of the country, the development of critical thinking. The article draws attention to the problem of reforming education in societies in the context of the dominance of moral relativism, the problematic aspects of the coexistence of contradictory traditions in society. It considers the peculiarities of education systems shaped by Marxist and post-Marxist ideologies. The paper emphasizes their connection with irrationalism and relativism. It also characterizes the formal way of organizing such a system and its value content. The article updates the categories of “social adaptation”, “social mimicry”, highlights the phenomenon of double moral standards of the post-totalitarian countries. It considers the principles of the strategy of the piecemeal social engineering for societies of such type. It covers the problematic aspects of the moderate (piecemeal) way of reforms and the method of radical transformations. It outlines the strategy of the constructive activity of the reformer, the features of his belonging to the critical-rationalist tradition. It emphasizes the role of philosophical education and philosophical disciplines in spreading values and ideals of the open society and the establishment of the rationalist tradition.
Keywords: Open society; rationality; critical thinking; piecemeal social engineering; education reform; social mimicry